Synthesis of New7-ethyl-4-methyl-2-Quinolone Derivatives - Ahamed, Luma S; Ali, Rana Abid; Ahmed, Rana S; Ahamad, Mohammed R; Al-Bayati, Redha I (Al-Nahrain Journal of Science, 2019)
A series of new derivatives of 7-ethyl-4-methyl quinoline-2-one were synthesized, by cyclization reaction of m-ethyl phenol with ethylacetoacetate in the presence of sulfuric acid to yield 7-ethyl-4-methyl coumarin, which was chosen as the starting material and it was treated with hydrazine hydrate 80% to give a new compound 1-amino-4 methyl-7- ethyl quinoline-2(1H)-one. The later compound introduced in different synthetic methods to produce new 4-methyl-7-ethyl-2-qunolone derivatives containing amide, imine, and acetylenic groups (L4-L10). Synthesized compounds were characterized by FT-IR, 1H-NMR, 13C-NMR spectra and by measuring some of their physical properties.